2021
DOI: 10.3390/genes12091396
|View full text |Cite
|
Sign up to set email alerts
|

Selective Breeding for Disease-Resistant PRNP Variants to Manage Chronic Wasting Disease in Farmed Whitetail Deer

Abstract: Chronic wasting disease (CWD) is a fatal transmissible spongiform encephalopathy (TSE) of cervids caused by a misfolded variant of the normal cellular prion protein, and it is closely related to sheep scrapie. Variations in a host’s prion gene, PRNP, and its primary protein structure dramatically affect susceptibility to specific prion disorders, and breeding for PRNP variants that prevent scrapie infection has led to steep declines in the disease in North American and European sheep. While resistant alleles h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 70 publications
(99 reference statements)
0
15
0
Order By: Relevance
“…Prnp polymorphisms have been shown to play a role in both scrapie and CWD susceptibility [44][45][46]. The white-tailed deer fetuses in this study were all codon 96 GG, and thus from current understanding, carry a genotype that supports CWD infection.…”
Section: Discussionmentioning
confidence: 73%
“…Prnp polymorphisms have been shown to play a role in both scrapie and CWD susceptibility [44][45][46]. The white-tailed deer fetuses in this study were all codon 96 GG, and thus from current understanding, carry a genotype that supports CWD infection.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, one strategy to minimize CWD spreading might be to perform selective breeding to produce animals with several polymorphic variants known to decrease infection. A recent study has shown that selective breeding might contribute to reduce CWD spreading [ 109 ]. A similar strategy was previously employed to attempt reducing prevalence of scrapie in sheep [ 110 ].…”
Section: Strategies For Minimizing Cwd Spreading: Is Eradication Of C...mentioning
confidence: 99%
“…In the case of sequencing PRNP in white-tailed deer, evidence of allelic dropout has recently been reported using one of the more commonly used primer sets. Researchers identified a polymorphism in the forward primer binding site [ 14 ] that prevents primer annealing leading to allelic dropout [ 27 ]. Ultimately, this leads to incorrect PRNP genotyping for deer carrying the primer binding site polymorphism [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers identified a polymorphism in the forward primer binding site [ 14 ] that prevents primer annealing leading to allelic dropout [ 27 ]. Ultimately, this leads to incorrect PRNP genotyping for deer carrying the primer binding site polymorphism [ 27 ]. Therefore, it is important to determine the extent of this polymorphism in the Illinois wild white-tailed deer population in order to determine its effect on the accuracy of previous Illinois PRNP published frequencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation